Perceptions, Experiences, and Hygiene Awareness Related to Menarche and Menstruation Among Adolescent Girls of Kathmandu Valley - Khadka, Kalpana; Giri, Sunita; Adhikari, Pramod; Yadav, Rakesh Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Background: Menstrual health and hygiene are critical to the well-being of adolescent girls. Understanding perceptions and practices surrounding menarche and menses within educational settings, such as the contrasting environments of public and private schools, is essential for developing targeted support systems. Objectives: This study aimed to compare the perception, emotional experience, and hygiene awareness of adolescent girls regarding menarche and menstruation between public and private secondary schools in Kathmandu Valley. Specific aspects investigated included emotional experiences at menarche, communication patterns, menstrual regularity, pain severity, prior familiarity with menarche, and hygiene practices. Methods: A quantitative, descriptive, and explanatory research methodology was employed. Data were collected from 504 students selected via simple random sampling from public and private secondary institutions in Kathmandu Valley. Findings: Key differences emerged between school types. Public school students were more likely to perceive menarche as a normal physiological event, whereas private school students reported being "terribly frightened" at first menstruation. Menstrual patterns were significantly more regular among public school students. Although a higher proportion of private school students reported severe menstrual pain, this difference was not statistically significant. Hygiene practices were generally good but significantly better among public school students. While private school students had higher familiarity with menarche prior to its onset, gaps remained in their emotional preparation and the translation of knowledge into consistent hygiene practices. The initial confidante (often the mother) did not differ between school types. Conclusion: The study concludes that significant disparities exist in menstrual experiences and practices between public and private school students in this setting. It underscores the need for intensified, standardized school-based menstrual health education that addresses not only knowledge but also emotional preparedness and the consistent application of healthy hygiene practices. Novelty: This research provides a direct comparative analysis of menstrual health perceptions and practices between public and private educational systems in Nepal. It highlights that higher socioeconomic status (associated with private schooling) does not inherently translate to better emotional or practical menstrual health outcomes, revealing a critical gap between knowledge acquisition and its emotional integration and practical application.